2024
DOI: 10.3389/fpubh.2024.1343350
|View full text |Cite
|
Sign up to set email alerts
|

A first insight into tuberculosis transmission at the border of Ecuador and Colombia: a retrospective study of the population structure of Mycobacterium tuberculosis in Esmeraldas province

Bernardo Castro-Rodriguez,
Sebastián Espinoza-Andrade,
Greta Franco-Sotomayor
et al.

Abstract: ObjectiveTuberculosis (TB) is a major public health concern in Ecuador and Colombia, considering that both countries are high-burden TB settings. Molecular epidemiology is crucial to understand the transmission dynamics of Mycobacterium tuberculosis complex (MTBC) and to identify active transmission clusters of regional importance.MethodsWe studied the potential transmission of TB between Colombia and Ecuador through the analysis of the population structure of MTBC lineages circulating in the Ecuadorian provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…Although some biological advantages that improve virulence and transmissibility over other genotypes has been described for MTB RD Rio (36,44,45), this could explain its successful transmission in some countries like Venezuela, Brazil, Peru and Colombia, but not in Ecuador (22,46,47). In fact, two recent studies have shown a very limited transnational transmission of MTB between Ecuador, Colombia and Peru that would also explain the low prevalence of MTB RD Rio sublineage found in our study (48,49). The phylogenetic analysis of MTBC RD Rio strains identified in Ecuador suggests a regional cluster associated to provinces in the Coastal Region but with an elevated genetic diversity and lack of active transmission chains.…”
Section: Discussioncontrasting
confidence: 51%
“…Although some biological advantages that improve virulence and transmissibility over other genotypes has been described for MTB RD Rio (36,44,45), this could explain its successful transmission in some countries like Venezuela, Brazil, Peru and Colombia, but not in Ecuador (22,46,47). In fact, two recent studies have shown a very limited transnational transmission of MTB between Ecuador, Colombia and Peru that would also explain the low prevalence of MTB RD Rio sublineage found in our study (48,49). The phylogenetic analysis of MTBC RD Rio strains identified in Ecuador suggests a regional cluster associated to provinces in the Coastal Region but with an elevated genetic diversity and lack of active transmission chains.…”
Section: Discussioncontrasting
confidence: 51%